Effect of Plant Density on Root Distribution of Three-Year-Old Grafted 99 Richter Grapevines - Archer, E.; Strauss, H. C. (South African Journal of Enology and Viticulture, 2017)
The effect of plant density on root distribution of a three-year-old vineyard (Pinot noir /99 Richter) planted on a Glenrosa soil under dryland conditions, was investigated. Although narrower plantings induced smaller root systems per vine, root density was increased. Three years after planting the roots of more closely spaced vines utilised soil more intensively than those of more widely spaced vines. More closely spaced vines have an earlier vegetative period than more widely spaced vines. The ratio of primary, secondary and tertiary roots is not affected by plant density.